Optimalisasi Biaya Metode-Metode Penghimpunan Dana Zakat, Infak, dan Sedekah LAZ Daarut Tauhiid Peduli Bogor - Fauzan Fadhil Ma'ruf; Tuti Kurnia (Institut Agama Islam Yasni Bungo, 2021)
The purpose of this study was to determine how to optimize the costs of the methods of collecting Zakat, Infaq, and Shadaqah (ZIS) funds at LAZ Daarut Tauhiid Peduli Bogor. The research method used is descriptive method with quantitative approach. Data collection techniques obtained through observation, interviews, and documentation. While the data analysis techniques used are Break Even Point (BEP) analysis and analysis of Strength, Weakness, Opportunity, and Threat (SWOT Analysis). The result obtained from this study are optimization of the cost of the method is quite good because ZIS revenue is quite high, so it must be maintained so that there is no decline in the future as experienced in 2018-2019. Based on the results of research rationally, it can be seen that the most optimal method that must be maximixed in collecting ZIS funds is the method of collecting through zakat pick-up which is Rp. 346,174,117 because the costs incurred are the smallest but the revenue is quite large. Keywords : Optimization, Collection Method, ZIS.